2018
DOI: 10.3390/su11010070
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Modified Sulfur Concrete for Achieving Sustainability in Industry Applications

Abstract: Portland cement concrete (PCC) has been the most widely used concrete in the construction industry. However, PCC has a short service life under some aggressive environments, leading to the need of costly repairs. The purpose of this research was to implement local materials to produce a modified sulfur concrete (MSC) with better performance in industrial applications. Several modified sulfur concrete mixtures were prepared using natural aggregates from the northern region of Colombia, and sulfur cement by comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…This analysis is used to identify the mineralogical composition which could possibly form during the hardening period [ 16 , 25 ]. The mineralogical matrix of sulfur-based concrete after one day of batching has major constituents like sulfur and silica while minor components are plagioclase, calcite, hematite, dolomite and hydrate of aluminum oxide [ 124 ]. High mechanical strength of sulfur-based concrete is justified by the availability of alumino and calcium alumino silicates in their respective oxides like SiO 2 , Al 2 O 3 and CaO.…”
Section: Sulfur In the Concrete Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis is used to identify the mineralogical composition which could possibly form during the hardening period [ 16 , 25 ]. The mineralogical matrix of sulfur-based concrete after one day of batching has major constituents like sulfur and silica while minor components are plagioclase, calcite, hematite, dolomite and hydrate of aluminum oxide [ 124 ]. High mechanical strength of sulfur-based concrete is justified by the availability of alumino and calcium alumino silicates in their respective oxides like SiO 2 , Al 2 O 3 and CaO.…”
Section: Sulfur In the Concrete Industrymentioning
confidence: 99%
“…Much research has been done to increase the effectiveness of sulfur in concrete production and it has been proven that this waste has useful value for various applications [ 35 , 127 ]. In 2011, Sabour et al [ 124 ] investigated sewage pipes made of sulfur-based concrete. The results showed that sulfur-based concrete was significantly more resistant to strong acid effects (chemical corrosion) compared to cement concrete but less resistant to the effects of microbial corrosion.…”
Section: Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantage in this method is the difficulty of impregnation from the molten state. Currently, products impregnated with molten sulfur are used in special cases when it is necessary to protect concrete from aggressive environments (acidic environments and saline solutions) [21][22].…”
Section: Main Partmentioning
confidence: 99%
“…In order to overcome this deficiency, with a bigger nominal concrete cover, to avoid corrosion of the reinforcement concrete, it was applied in concrete the corrosion inhibitors. Corrosion inhibitors are useful in cases where it is not possible to achieve full concrete cover on the reinforcement; however, they raise the price of the sleeper [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%